Bridging adjuvant treatment gaps: low and intermediate risk endometrial carcinoma patients care in Salah Azaiez Institute in Tunisia - Boudhina, Emna; Zarraa, Semia; Sahraoui, Ghada; Mousli, Alia; Ben Zid, Khadija; Ghorbel, Asma; Yousfi, Ameni; Abidi, Rim; Yahiaoui, Safia; Nasr, Chiraz (The oncologist (Dayton, Ohio), 2025)
Abstract Background The management of low- and intermediate-risk endometrial carcinoma (EC) at the Salah Azaiez Institute (SAI) has evolved with international recommendations and the advent of the molecular era. We lack access to molecular profiling; consequently, both undertreatment and overtreatment are observed. This study explores how adherence to international recommendations affects clinical outcomes. Methods We performed a retrospective analytic study including 180 women with stage I–II low-, low-intermediate-, and high-intermediate-risk EC treated at SAI between 2015 and 2020, with at least 3 years of follow-up. Ethical approval and patient consent were obtained; for telephone interviews, verbal consent was secured. We selected 60 women per risk group from a larger pool to ensure comparability. Eleven histopathologic slides exhibiting lymphovascular space invasion (LVSI) were reviewed independently by 2 experienced pathologists to distinguish focal from extensive LVSI; no slides without LVSI were reexamined. Risk stratification followed the 2020 ESGO–ESTRO–ESP guidelines, and adjuvant treatments were assessed according to the 2021 ESGO–ESTRO recommendations. Pelvic lymphadenectomy was the standard nodal assessment; sentinel lymph node (SLN) mapping was not available during the study period. Results Median age was 60 years (range 35–69). After histopathologic review, 51.1% of tumors were grade 2, 54.5% had under 50% myometrial invasion, 8.3% had extensive LVSI, and 3.9% had focal LVSI. Forty-seven per cent of patients received guideline-concordant therapy, 47% were over-treated, and 6% were under-treated. Over-treated women had a 7.9-fold higher risk of death and a 6.6-fold higher risk of recurrence than appropriately treated women. Under-treatment was not a significant prognostic factor. Overtreatment and guideline-concordant therapy were both associated with higher rates of gastrointestinal, genitourinary, and sexual toxicities. Conclusion Limited access to molecular profiling constrains personalized care in Tunisia. Strict adherence to current guidelines is essential to avoid unnecessary toxicity, and the integration of molecular classification and SLN mapping should be prioritized.